Jüdische Wissenskulturen und Allgemeine Literaturwissenschaft - Olk, Claudia; Zepp, Susanne (De Gruyter, 2022)
Works that had a considerable impact on the development of the humanities in the twentieth century emerged against the backdrop of a culture of knowledge and an epistemological history shaped by Judaism. This volume aims to document this development without simply comparing origins, belonging, and styles of thought, instead tracing a textual scholarship that provided new access to literature and literary studies.